Analysis Of The Influence Of Corporate Social Responsibility On Consumer Loyalty Through Brand Image, Brand Equity, And Consumer Satisfaction - Fadhilah, Siti; Anggraeni, Dewi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the influence of corporate social responsibility on consumer loyalty, mediated by brand image, brand equity, and consumer satisfaction. The research involved 208 respondents selected through purposive sampling, with criteria including consumers who had used Lifebuoy products for at least 6 months, aged between 20 - 40 years, and residing in Tangerang. Data were collected online through a Google Form questionnaire and analyzed using the PLS-SEM method. The results indicate that corporate social responsibility does not have a direct effect on consumer loyalty. However, corporate social responsibility has a positive influence on brand image, brand equity, and consumer satisfaction. Among these three mediating variables, only consumer satisfaction is found to significantly mediate the relationship between corporate social responsibility and consumer loyalty. These findings suggest that companies should integrate corporate social responsibility into their marketing strategies, with an emphasis on effective communication to enhance consumer satisfaction and foster stronger emotional connections.